Towards hermeneutics of substantial change. Between conciliar continuity and tendency to break - Napiórkowski, Andrzej (Analecta Cracoviensia, 2015)
In the interpretation of Revelation, as well as, documents of the Magisterium of the post-conciliar Catholic theology, strong tensions and differences have been exposed.They are a consequence of various hermeneutics. Each of the sides claims the right to define "a reform".However, a careful and critical analysis of the three functioning types of hermeneutics (of absolute continuity, of a break, and of absolute fidelity to the tradition) is not fully satisfactory.In its external form of expression the symbols and dogmas of faith are historical, so with the flow of history they become anachronistic, despite the fact that the essence (the core) of the doctrine is not changed, because it comes from the Divine Revelation and is a subject of personal experience of the faithful. Therefore, a fundamental basis of faith lies in the event of Revelation, namely, the self-giving of the Triune God. Hence the Revelation must be understood not as a statement of truth, but as an event of truth. It is about personal experience of the Resurrected, and not just knowledge or information about Him. Therefore, the language and the manner of communication must be constantly verified and contemporized. While the truth is always not completely grasped. This is why the presented article is a small contribution in developing a fourth type of hermeneutics - a hermeneutics of substantial change, which though would allow to break the continuity at some points, nevertheless would not destroy the identity of faith.